2002
DOI: 10.1177/13670069020060040201
|View full text |Cite
|
Sign up to set email alerts
|

Nonparellel recovery of languages in a quadrilingual aphasic patient

Abstract: This case study aims to investigate whether the treatment of only one language (L2) of a multilingual fluent aphasic(L1 Slovenian, L2 Italian, L3 Friulian, L4 English) results in a parallel improvement of all languages and whether the hypothesized benefits of rehabilitation last four years after the end of treatment. After a first assessment by means of the Aachener Aphasie Test (AAT) and the Bilingual Aphasia Test(BAT), the patient has been treated for six months in Italian(L2), subsequently tested again, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…One study preliminarily accepted (Fabbro, Deluca, & Vorano, 1996) could not be obtained despite attempted correspondence with authors. An additional treatment study (Filiputti et al, 2002) could not be included in our data analysis because it only provided overall language measures (for morphology, syntax, etc.) that were derived by combining expressive and receptive scores.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…One study preliminarily accepted (Fabbro, Deluca, & Vorano, 1996) could not be obtained despite attempted correspondence with authors. An additional treatment study (Filiputti et al, 2002) could not be included in our data analysis because it only provided overall language measures (for morphology, syntax, etc.) that were derived by combining expressive and receptive scores.…”
Section: Literature Searchmentioning
confidence: 99%
“…Unilingual therapy is also recommended for individuals who experience pathological code-mixing/code-switching or who live in a primarily monolingual environment (Abutalebi & Green, 2008;Ansaldo, Ghazi Saidi, & Ruiz, 2009). However, this prediction of cross-language transfer (CLT) with unilingual therapy has not been consistently borne out (e.g., Edmonds & Kiran, 2006;Faroqi & Chengappa, 1996;Filiputti, Tavano, Vorano, De Luca, & Fabbro, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been claimed that rehabilitation efforts usually tend to transfer from the trained to the untrained language to some degree (Fabbro, 2001b;Filiputti, Tavano, Vorano, de Luca, & Fabbro, 2002;Fredman, 1975;Gil & Goral, 2004;Watamori & Sasanuma, 1978), the improvement in the trained language is usually more pronounced than in the untrained language. For example, Junque, Vendrell, Vendrell-Brucet, and Tobena (1989) found more enhanced improvement of naming performance for the trained language in a sample of 30 Catalan-Spanish bilingual aphasics.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment in L2 resulting in improvement in the untreated L1 (Faroqi & Chengappa, 1996;Fredman, 1975;Gil & Goral, 2004;Linke, 1979;Marangolo et al, 2009;Penn & Beecham, 1992;Voinescu et al, 1977) or untreated L3 (Filiputti et al, 2002;Goral et al, 2010;Voinescu et al, 1977) has also been reported. Gil and Goral (2004) investigated therapy transfer for a late proficient bilingual speaking Russian (L1) and Hebrew (L2) with aphasia that resolved from expressive-receptive to amnestic in L1 and L2.…”
Section: Introductionmentioning
confidence: 92%
“…Cross-language therapy transfer studies 2.1. Evidence of therapy transfer across languages Treatment in one language resulting in improvement of the untreated language has been reported in a range of studies (Chlenov, 1948;Durieu, 1969;Edmonds & Kiran, 2006;Faroqi & Chengappa, 1996;Filiputti, Tavano, Vorano, de Luca, & Fabbro, 2002;Fredman, 1975;Gil & Goral, 2004;Goral et al, 2010;Hinckley et al, 2005;Junqué, Vendrell, Vendrell-Brucet, & Tobeña, 1989;Kiran & Edmonds, 2004;Kohnert, 2004;Laganaro & Overton-Venet, 2001;Linke, 1979;Marangolo, Rizzi, Peran, Piras, & Sabatini, 2009;Miertsch et al, 2009;Penn & Beecham, 1992;Voinescu, Vish, Sirian, & Maretsis, 1977). The majority of these studies have focused on the effects of treatment for naming or spoken expression, with therapy provided in the first or the second language.…”
Section: Introductionmentioning
confidence: 94%